THE ROLE OF LACTASE INSUFFICIENCY AND INTESTINAL MICROFLORA IN DEVELOPMENT OF GASTROINTESTINAL DYSFUNCTIONS IN INFANTS AGED 0–6 MONTHS OLD - E. A. Kornienko; S. S. Kubalova (Вопросы современной педиатрии)
Aim: to determine the role of lactase insufficiency (LI) and microbial imbalance (MI) in functional disorders of the gastrointestinal dysfunctions (GIF) in infants. Patients and methods: 102 children from the observed population of 268 infants aged 0–6 month old were examined more thoroughly. They were divided into 2 groups: control group of healthy children (n = 40) and 62 patients corresponding the Rome criteria III on GIF in children (study group). Results: regurgitation and intestinal colic predominated among GIF, in 71% of cases they were associated. LI was found in 37% of children with GIF У 37%.Clinical manifestations of GIF were similar both in patients with and without LI. In all children with LI and in 85% of children without LI there was complicated pregnancy history. Intestinal microbiocenosis imbalance (increased amount of conditionally pathogenic flora) was found in all children with GIF, however the results of cultural investigation of faeces and polymerase chain reaction did not coincide with each other. Calprotectin concentration was increased in all children with GIF, especially in LI (522,21 ± 27,84 mcg/g). Treatment management depended on feeding type and presence of LI: in cases of LI patients were administered β-galactosidase, in infants without LI probiotic strains included into milk formulas or drugs were used. In all cases clinical improvement, decrease of calprotectin concentration and improvement of microbiological signs were observed. Conclusions: transitory LI was found more than in 1/3 of the patients with GIF symptoms, moreover the clinical manifestations are similar, which requires additional examination. The optimal diagnostic test is lactose hydrogen breath test. All children with GIF have intestinal microbiocenosis imbalance and symptoms of mild intestinal inflammation. Correction of GIF should be performed in accordance with LI. Lactase enzyme effectively eliminates both LI symptoms and inflammation signs.